Docosahexaenoic acid (DHA) production by Aurantiochytrium limacinum using cassava pulp hydrolysate as an alternative low-cost carbon source - Aini, Uyun Nurul; Lunprom, Siriporn; Reungsang, Alissara; Salakkam, Apilak (Frontiers in Marine Science, 2022)
Cost of nutrients is one of the major contributors to the production cost of docosahexaenoic acid (DHA) by thraustochytrids, and this remains the main challenge for economical and sustainable production of DHA. In the present study, cassava pulp (CP) was investigated as an alternative low-cost carbon source for DHA production by Aurantiochytrium limacinum SR21. Cultivation conditions, i.e., salinity level, type of nitrogen source, and concentrations of glucose and nitrogen sources, as well as pH, were optimized for cell growth. CP was enzymatically hydrolyzed, and used as the base medium, supplemented with artificial seawater salts, for DHA production under fed-batch cultivation. A. limacinum grew well at 18 g/L of NaCl (equivalent to 50% salinity level), and initial glucose concentration of 64 g/L, initial yeast extract concentration of 5 g/L, and pH 7.5 were optimum for cell growth. Fed-batch cultivation, with dissolved oxygen (DO) controlled at 10%, using CP-based medium as the carbon source gave a final cell dry mass of 26.3 ± 2.0 g/L, with 15.5 ± 0.1 g/L of lipid. DHA content in the lipid was 37.4 ± 1.5%, equivalent to 5.8 ± 0.3 g/L, and DHA productivity was 960 mg/(L·d). Medium-based economic analysis showed that an economic yield (EY) of this process was 0.86, which was higher than the 0.81 obtained using glucose as the substrate, assuming the same process and conditions. Overall, the results reveal that CP is a highly feasible feedstock for DHA production by A. limacinum SR21.